Code-Switching as Indexical of Native Language Lexical Deficiency in Mauritania - Sounkalo, Jiddou (Journal of multilingual and multicultural development, 1995)
Investigates the relationship between French instruction and the phenomena of discontinued lexical development, lexical attrition, and lexical deficiency in the speech of Mauritanians. Findings indicate native-language lexical deficiency was reflected in code switching, and subjects (Ss) with low native-language fluency code switched more than Ss with high native fluency. (38 references) (Author/CK)